Faktor – Faktor yang Mempengaruhi Imunisasi Lengkap pada Anak Balita di Wilayah Kerja UPTD Puskesmas Sawang Kabupaten Aceh Utara - Ully Fitria; Rahmad Haris; Ambia Nurdin; Mirna Yulia; Khairuman Khairuman (Lembaga Pengembangan Kinerja Dosen, 2025)
Immunization is one of the important disease prevention efforts for toddlers. Complete immunization in toddlers can prevent various diseases that can be high-risk for children's health, such as diphtheria, polio, hepatitis, and measles. However, the level of complete immunization coverage in toddlers in Indonesia, including in the working area of ​​the UPTD Sawang Health Center, North Aceh Regency, is still a challenge. This study aims to identify factors that influence the implementation of complete immunization in toddlers in the area. The method used in this study is quantitative research with a descriptive approach. The research sample consisted of parents or caregivers of toddlers in the working area of ​​the UPTD Sawang Health Center, with a total of 100 respondents. Data were collected through a questionnaire that included factors such as parental knowledge, attitudes, accessibility of health services, and family socio-economic factors. Data analysis was carried out using descriptive statistics. The results of the study showed that there were several factors that influenced complete immunization in toddlers, namely parental knowledge about the importance of immunization, parental attitudes towards immunization, accessibility to health facilities, and parental education levels. Socioeconomic factors, such as family income and parental occupation, also played an important role in the success of complete immunization. In addition, there was a significant influence between the distance from the house to health facilities on the level of immunization coverage. From the results of this study, it can be concluded that efforts to increase the coverage of complete immunization in toddlers in the Sawang Health Center UPTD area need to consider these factors.